Final adult height and endocrine complications in young adults with β-thalassemia major (TM) who received oral iron chelation (OIC) in comparison with those who did not use OIC - Soliman, Ashraf T; Yassin, Mohamed A; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2018)
Background: Relatively little is known about endocrine function, bone mineral health, and growth during oral iron chelation therapy in β-thalassemia major patients (TM) on treatment with deferasirox. Aims of the study: To study the frequency of endocrine complications, IGF-1 levels and final adult standing height (FA-Ht) in patients with BTM in two groups of adult patients. Patients and methods: The first group (Group A; 15 patients, 6 females and 9 males) received oral iron chelation therapy (OIC) with deferasirox for 6 years before puberty; the second group (Group B;40 patients) attained the FA-Ht before the use of OIC (iron chelation therapy with deferoxamine (DFO) given subcutaneously, since the age of 2 years). In both groups liver iron concentration was measured using FerriScan ® R2-MRI method. Furthermore, the FA-Ht, bode mass index (BMI), and insulin growth factor-1 (IGF-1) in a selected group of adult patients [9 with normal growth hormone (GH) secretion (GHN) and 8 with GH deficiency (GHD; peak GH response to provocative test with clonidine: < 7 ng/ml), who were on iron chelation therapy with DFO given subcutaneously that was changed to oral deferasirox during the last 5-6 years. These 15 patients were not treated with rhGH. Results: Adults with BTM who received OIC for 6 years or more before attaining their FA-Ht, had lower liver iron concentration (LIC) assessed by FerriScan® R2-MRI, fasting glucose level (FBG) and liver enzymes (ALT and AST), and a better FA-Ht expressed in standard deviation score (FA-Ht-SDS), and higher IGF-1 SDS versus those who did not receive OIC before attaining FA-Ht. The prevalence of endocrinopathies, including hypothyroidism and hypogonadism were significantly lower in Group A versus Group B. Comparison between the group with normal GHN and those with GHD showed that the FA-Ht-SDS of those with GHD (159.1± 6.42 cm). Ht-SDS = -2.5 ± 0.9) was significantly decreased compared to the group with NGH (Ht = 163.5 ± 5.2 cm, Ht-SDS = -1.74 ± 0.83). The IGF-1-SDS did not differ between the two groups. Neither ferritin level nor IGF-1 concentrations were correlated with the Ht-SDS. The final FA-Ht-SDS correlated significantly with the peak GH secretion (r = 0.788, p = 0.0008). The FA-Ht-SDS were positively related to their mid-parental height (r=0.58, P <0.01). Conclusions: The use of OIC years before the end of puberty was associated with a significantly lower prevalence of endocrinopathies, improvement of LIC and FA-Ht. The final adult height of patients with BTM and GHD was significantly shorter compared to their pears with NGH. rhGH therapy can be recommended for the treatment of thalassemic children and adolescents with GHD in addition to proper blood transfusion and intensive chelation to improve their final height.